Answer:
![\frac{5}{4}+or-\frac{3i\sqrt{7} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%2Bor-%5Cfrac%7B3i%5Csqrt%7B7%7D%20%7D%7B4%7D)
Step-by-step explanation:
You can solve this equation with the quadratic formula which is:
![m_{1,2}=\frac{-b+or-\sqrt{b^{2}-4ac } }{2a}](https://tex.z-dn.net/?f=m_%7B1%2C2%7D%3D%5Cfrac%7B-b%2Bor-%5Csqrt%7Bb%5E%7B2%7D-4ac%20%7D%20%7D%7B2a%7D)
All you need to do is rearrange the equation (add
to both sides and then multiply both sides by 2) to get:
![2m^2-5m+11=0](https://tex.z-dn.net/?f=2m%5E2-5m%2B11%3D0)
From this new equation, we can easily see that a = 2, b = -5, and c = 11 AND you don't have to work with as many fractions. Substitute the values for a, b, and c into the quadratic formula to get:
![m_{1,2}=\frac{5+or-\sqrt{(-5)^{2}-4(2)(11) } }{2(2)}](https://tex.z-dn.net/?f=m_%7B1%2C2%7D%3D%5Cfrac%7B5%2Bor-%5Csqrt%7B%28-5%29%5E%7B2%7D-4%282%29%2811%29%20%7D%20%7D%7B2%282%29%7D)
That simplifies to:
![\frac{5}{4}+or-\frac{\sqrt{25-88} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%2Bor-%5Cfrac%7B%5Csqrt%7B25-88%7D%20%7D%7B4%7D)
Which simplifies even further to:
![\frac{5}{4}+or-\frac{\sqrt{-63} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%2Bor-%5Cfrac%7B%5Csqrt%7B-63%7D%20%7D%7B4%7D)
Which gets you:
![\frac{5}{4}+or-\frac{3i\sqrt{7} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%2Bor-%5Cfrac%7B3i%5Csqrt%7B7%7D%20%7D%7B4%7D)
P.S. The plus-minus sign wasn't working for me, so I had to just write, "+or-". I hope that didn't make it too confusing for you.
P.P.S. Hope this helps :) Don't forget to mark Brainliest if it did.
Answer:
$11.25
Step-by-step explanation:
5 bags = $18.75
To find the amount for three bags, we need to find the price for <em>each </em>bag.
Divide 18.75 by 5.
18.75/5 = 3.75
So each bag is 3.75, and since we need to know the price for 3 bags, we need to multiply 3.75 by 3, which is 11.25.
131.7625 would be your answer here
There are only two possible outcomes in the table that satisfy <em>x</em> ≤ -3; either <em>x</em> = -5 or <em>x</em> = -3. Then
P(<em>x</em> ≤ -3) = P(<em>x</em> = -5) + P(<em>x</em> = -3) = 0.17 + 0.13 = 0.3
Ummm there’s no right triangular